2012
DOI: 10.1159/000343930
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Reactivity to Film Material in Alzheimer’s Disease

Abstract: Aims: To explore emotional reactivity in mild to moderate Alzheimer’s disease (AD) using film material, investigating the influence of dementia-related material and awareness of condition. Methods: Twenty-two patients with AD and 21 healthy older adults viewed films with positive, neutral or negative content, including a film about dementia. Reactivity was measured through a self-report questionnaire and filming of facial expressions. Awareness of condition was assessed contrasting patients’ versus informants’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…When they only received a warning, but no instructions to down-regulate (Condition 2), it appeared that only AD patients and healthy controls were successful in inhibiting their facial responses. This finding of deficient inhibition of facial expressions in dementia is supported by some [55], but not all [56,57], studies.…”
Section: Disinhibitionsupporting
confidence: 60%
“…When they only received a warning, but no instructions to down-regulate (Condition 2), it appeared that only AD patients and healthy controls were successful in inhibiting their facial responses. This finding of deficient inhibition of facial expressions in dementia is supported by some [55], but not all [56,57], studies.…”
Section: Disinhibitionsupporting
confidence: 60%
“…Third, while watching the films, the patients displayed emotional behaviors, such as crying or laughing, that were consistent with the feelings that they later reported. Previous studies looking at emotional reactivity in patients with AD have also shown preserved facial responses to emotional film clips (Mograbi et al, 2012; Smith, 1995). …”
Section: Discussionmentioning
confidence: 91%
“…Since MCI mainly affects the medial temporal and frontal structures normally involved in encoding emotional stimuli, a reduction in EEF would be expected. Nevertheless, neuroanatomical [25,26] and behavioural findings are still controversial [22,[27][28][29][30], possibly due to the different methodologies employed.…”
Section: Introductionmentioning
confidence: 99%